2008
DOI: 10.1002/cpp.575
|View full text |Cite
|
Sign up to set email alerts
|

Therapist technique and patient defensive functioning in ultra‐brief psychodynamic psychotherapy: a lag sequential analysis

Abstract: This study examined the association between therapist interventions, including interpretations, and patient defensive functioning. The first session of 32 (n = 32) Brief Psychodynamic Interventions were rated for therapist interventions and patient defensive functioning. Lag sequential analysis was used to determine if (a) there are organized sequences of therapist interventions; (b) there are predictable sequences in the patients' level of defensive functioning; (c) there are sequences of therapist interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
(30 reference statements)
2
18
1
Order By: Relevance
“…Lag-sequential analysis has been widely used in research, specific topics include: foraging patterns in animal behavior research (Butler, 2005), children’s mealtime behaviors before and after parental attention (Woods, Borrero, Laud, & Borrero, 2010), transition patterns of preschooler’s social play (Robinson, Anderson, Porter, Hart, & Wouden-Miller, 2003), precursors of problem behavior in individuals with autism (Borrero & Borrero, 2008), sequences in therapist’s intervention and patient’s levels of defensive functioning (Drapeau, de Roten, Beretta, Blake, Koerner, & Despland, 2008), online asynchronous problem-solving discussion patterns (Hou, Chang, & Sung, 2008), patterns of work group discussions about complaints and solutions (Kauffeld & Meyers, 2009), and communication sequences that contribute to better team performance (Bowers, Jentsch, Salas, & Braun, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Lag-sequential analysis has been widely used in research, specific topics include: foraging patterns in animal behavior research (Butler, 2005), children’s mealtime behaviors before and after parental attention (Woods, Borrero, Laud, & Borrero, 2010), transition patterns of preschooler’s social play (Robinson, Anderson, Porter, Hart, & Wouden-Miller, 2003), precursors of problem behavior in individuals with autism (Borrero & Borrero, 2008), sequences in therapist’s intervention and patient’s levels of defensive functioning (Drapeau, de Roten, Beretta, Blake, Koerner, & Despland, 2008), online asynchronous problem-solving discussion patterns (Hou, Chang, & Sung, 2008), patterns of work group discussions about complaints and solutions (Kauffeld & Meyers, 2009), and communication sequences that contribute to better team performance (Bowers, Jentsch, Salas, & Braun, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Although adaptive defenses did increase in the sample, neither the use of support nor the use of interpretive techniques explained the change. In a study of ultra-brief psychodynamic psychotherapy using sequential analysis, it was determined that therapists typically use supportive interventions to "prepare" patients before making defense interpretations [77]. That study also found that there are predictable ways in which psychodynamic therapists structure and use therapeutic interventions.…”
Section: Balance Between Supportive and Interpretive Interventionsmentioning
confidence: 99%
“…Several studies [6][7][8] have been drawn to lag sequential analysis in an attempt to capture a more accurate view of how the use of therapeutic techniques in psychotherapy actually transpires. Using lag analysis, Milbrath and colleagues [7] found that therapists structured their interventions around patient level of subjective distress and functioning.…”
mentioning
confidence: 99%
“…Drapeau and colleagues [6] found that both therapists' use of interventions and patients' use of defenses could be segmented into predictable chains of sequences. However, they failed to find an interaction between the two.…”
mentioning
confidence: 99%
See 1 more Smart Citation